IMPLEMENTATION OF ALTMAN Z-SCORE IN PREDICTING PT BANK SUMUT'S SUSTAINABILITY - Simatupang, Eva Malina (Accounting and Business Journal, 2020)
This research was conducted to determine and analyze the risk of bankruptcy of the company PT BankSUMUT according to the Altman Z-Score. The population in this study is the financial statements of PTBank SUMUT and the sample in this study is the financial statements of PT Bank SUMUT for 2017 -2019. The type of data used is secondary data and the data collection techniques used are documentationfrom financial reports published through the www site. banksumut.co.id. The data processing techniqueuses the Altman Z-Score modification method. Based on the results of data processing, the 2017 Z-Scorewas 1.57; the year 2018 is 1.63 and the year 2019 is 1.19. Based on the results of data analysis, it can beconcluded that PT Bank SUMUT is in a gray zone because the standard value is at 1.1 <Z-Score <2.6and PT.